Wetting and motion behaviors of water droplet on graphene under thermal-electric coupling field - Zhang, Zhong-Qiang; Dong, Xin; Ye, Hong-Fei; Cheng, Guang-Gui; Ding, Jian-Ning; Ling, Zhi-Yong (Journal of applied physics, 2015)
Wetting dynamics and motion behaviors of a water droplet on graphene are characterized under the electric-thermal coupling field using classical molecular dynamics simulation method. The water droplet on graphene can be driven by the temperature gradient, while the moving direction is dependent on the electric field intensity. Concretely, the water droplet on graphene moves from the low temperature region to the high temperature region for the relatively weak electric field intensity. The motion acceleration increases with the electric field intensity on graphene, whereas the moving direction switches when the electric field intensity increases up to a threshold. The essence is the change from hydrophilic to hydrophobic for the water droplet on graphene at a threshold of the electric field intensity. Moreover, the driven force of the water droplet caused by the overall oscillation of graphene has important influence on the motion behaviors. The results are helpful to control the wettability of graphene and further develop the graphene-based fluidic nanodevices.